Bunnicula : a rabbit-tale of mystery - Howe, Deborah, 1946-1978.; Howe, James, 1946-; Daniel, Alan, 1939- (New York : Aladdin Paperbacks, 1996)
Though scoffed at by Harold the dog, Chester the cat tries to warn his human family that their foundling baby bunny must be a vampire.
8-12.
Keywords: Rabbits -- Fiction; Vampires -- Fiction; Bunnicula (Fictitious character) -- Fiction; Mystery fiction